2018
DOI: 10.17051/ilkonline.2018.466358
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Matematik Öğrenme Yaklaşımlarının Belirlenmesi

Abstract: Çalışmanın amacı öğrencilerin matematik dersindeki öğrenme yaklaşımlarını belirlemeye yarayan bir ölçme aracı geliştirmek ve geliştirilen ölçek aracılığıyla ortaokul öğrencilerinin matematiği öğrenme yaklaşımlarını incelemektir. Bu araştırma hem bir ölçek geliştirme çalışması olup geliştirilen Matematik Öğrenme Yaklaşımları Ölçeği'nin geçerlik ve güvenilirlik çalışmalarını sunmaktadır hem de betimsel bir çalışma olup öğrencilerin matematik dersindeki öğrenme yaklaşımlarını araştırmaktadır. Araştırma 790 ortaok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
7
0
4
Order By: Relevance
“…In order for students to prefer the in-depth learning approach more in mathematics lessons a student-centered problem-based learning environment (Gordon & Debus, 2002;Sezgin-Selçuk, 2010), an inventive based teaching (Ünal & Ergin, 2006) and an environment with computer-aided materials (Tinker, 1997) need to be created. Therefore, in a classroom where students with a superficial or strategic learning approach are abundant, the teacher can direct their students to in-depth learning with different activities according to the teaching method they choose (Göktepe- Yıldız & Özdemir, 2018). As Biggs and Tang (2007) stated, by creating a better learning environment, more effective answers can be obtained from students, and teaching by presenting inquiry-based problems rather than teaching the information can encourage students to utilize in-depth learning approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order for students to prefer the in-depth learning approach more in mathematics lessons a student-centered problem-based learning environment (Gordon & Debus, 2002;Sezgin-Selçuk, 2010), an inventive based teaching (Ünal & Ergin, 2006) and an environment with computer-aided materials (Tinker, 1997) need to be created. Therefore, in a classroom where students with a superficial or strategic learning approach are abundant, the teacher can direct their students to in-depth learning with different activities according to the teaching method they choose (Göktepe- Yıldız & Özdemir, 2018). As Biggs and Tang (2007) stated, by creating a better learning environment, more effective answers can be obtained from students, and teaching by presenting inquiry-based problems rather than teaching the information can encourage students to utilize in-depth learning approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the 6 th grades, although the in-depth learning approach average scores are in favor of gifted students, this difference is not statistically significant. In their study Göktepe- Yıldız and Özdemir (2018), concluded that, as the grade level increases in students who are not diagnosed with giftedness, the tendency of the students to prefer the in-depth learning approach decreases and there is no difference in the students' preferring the superficial learning approach. The situation in this study may have been due to the ability of gifted students to ask more questions in their lessons and their will to reach the information themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diğer yandan öğrencilerin matematiğe yönelik tutumları üzerinde; matematiksel ilişkilendirme öz-yeterlik, matematik öğrenme yaklaşımları ve temel psikolojik ihtiyaçlar doğrudan anlamlı pozitif bir etki göstermiştir. Elde edilen bu bulgu, öz-yeterlik, psikolojik ihtiyaçlar ve öğrenme yaklaşımları ile ilgili alanyazında yer alan kuramsal açıklamalar ve yapılan çalışmalarla örtüşmektedir (Abalı-Öztürk ve Şahin, 2015; Bandura, 1997;Deci ve Ryan, 1985;Durmaz ve Akkuş, 2016;Göktepe-Yıldız ve Özdemir, 2018;Kaya, 2018;Özgen ve Bindak, 2018;Peker ve Aydın, 2003;Schunk, 2011;Zimmerman, 1995). Öz-yeterlik inancı bireyin kendine olan güvenini artırır, öğrenme düzeyinin yükselmesine ve davranışlarının geliştirmesine yardımcı olur (Bandura, 1997;Pajares ve Miller, 1994).…”
Section: Tartişma Ve Sonuçunclassified